Chapter 10 Stealing the art of pain Body art and Zhao Yue's Lattice - Strafella, Giorgio (Taylor & Francis, 2023)
This chapter examines the emergence and reception in China of 'body art' (shenti yishu or routi yishu) - one of the most extreme and controversial artistic trends of the postsocialist era - as a transcultural phenomenon. This chapter frames 'body art' in 1990s-2000s China within the atmosphere of cynicism which prevailed in the years after the events of 1989 and the heightened role of the market in the cultural sphere. The chapter argues that the notion that it behoves the Party-state to protect the bodies and minds of the people from harmful cultural spectacles represents a residue of Mao-era socialism in the postsocialist era. To investigate the reception of 'body art' by the Chinese art world, this chapter analyses a performance by woman artist Zhao Yue (b. 1981) entitled Gezi (Lattice, or Grids, 2007) and discusses the debate this work elicited among Chinese art critics. Its analysis reveals body art from China as a cultural trend where postsocialist biopolitics and gendered cultural identities intersect with transcultural flows of artistic experimentation, thus highlighting key tensions that animate the intellectual life of contemporary China.